Evolution of superhump characteristics in SU UMa and nova-like variables - Andronov, I. L.; Baklanov, A. V.; Chinarova, L. L.; Kolesnikov, S. V.; Ostrova, N. I.; Yushchenko, A. V.; Niarchos, P. G.; Gazeas, K. D.; Shakhovskoj, N. M.; Pavlenko, E. P. (2003)
Recent highlights of our study of positive and negative superhumps in cataclysmic varibles are briefly reviewed. The ``genuine" superhumps have been detected a day after the unexpected superoutburst of WZ Sge, when the orbital variability dominated the light curve. TT Ari has shown an unprecedented switch form the usual negative superhump state to the positive state with an excellent coincidence between the observed and theoretically predicted period values. Both stars show evidence for variability at a time scale of 20 minutes. The superhump period of RZ LMi has been corrected based on the observations of the superoutburst in 2001. ES Dra shows no evidence for prominent superhumps, possibly indicationg its low inclination. However, the superoutburst has shown a splitted maximum with a separation of 20 days. The ``superhump period-luminosity" dependence has been detected for two cataclysmic variables of different types -- the nova-like BZ Cam and the UG SU star V368 Peg.